Hubungan Dukungan Teman Sebaya dengan Motivasi Pelaksanaan Vaksinasi Covid-19 pada Remaja di SMP Taman Dewasa Jetis, Sleman, Yogyakarta - Andunara, Afrianus; Wirata, Resta Betaliani; Palupi, Ethic; Prawesti, Indah (PENA NURSING, 2024)
Background: Motivation is a condition that activates a person's behavior. The preliminary study found that there were six students in one class who had not received the Covid-19 vaccination. The school has carried out vaccinations, but there are still some who have not been vaccinated because during an interview with one of the students he said he did not vaccinate because he was afraid of being injected and also followed his friend who had not had the Covid-19 vaccine.Objective: to determine the relationship between peer support and the motivation for the implementation of Covid-19 vaccination in adolescents at Taman Dewasa Jetis Middle School, Slemam, Yogyakarta.Method: The study design used a quantitative - correlation with a cross-sectional approach. The population is 230 people, the sampling technique is stratified random sampling. The number of samples is 49 respondents with a measuring instrument in the form of a questionnaire and using Spearman rank analysis.Finding: Spearman rank test results obtained p-value 0.419 (> 0.05). The results of the analysis test show that the p-value is greater than alpha.Conclusion: There is no relationship between peer support and the motivation for the implementation of Covid-19 vaccination in adolescents at Taman Dewasa Jetis Middle School, Slemam, Yogyakarta.